2023
DOI: 10.1007/s13555-023-00918-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Leukocytes, B and T Lymphocytes, and expression of CD200 and CD23 on B lymphocytes in Patients with Atopic Dermatitis on Dupilumab Therapy—Pilot Study

Abstract: Background There are a lot of studies that describe the change in quantity of T cells in patients with atopic dermatitis (AD) compared with healthy subjects. Other components of lymphocytes such as B cells are not examined as well as T cells. Objective We focus on immunophenotyping of B cells with their subsets (memory, naïve, switched, non-switched) and the expression of CD23 and CD200 markers in patients with AD with and without dupilumab therapy. We also evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
(76 reference statements)
2
1
0
Order By: Relevance
“…6 In our previous study, we evaluated the CD23 expression in B cells in AD patients. 7 We confirmed significantly higher expression of CD23 molecule on B lymphocytes and their subsets in AD patients with and without dupilumab therapy compared with controls. 7 The aim of this pilot study was to evaluate the association be- 1).…”
Section: Dear Editorsupporting
confidence: 67%
See 1 more Smart Citation
“…6 In our previous study, we evaluated the CD23 expression in B cells in AD patients. 7 We confirmed significantly higher expression of CD23 molecule on B lymphocytes and their subsets in AD patients with and without dupilumab therapy compared with controls. 7 The aim of this pilot study was to evaluate the association be- 1).…”
Section: Dear Editorsupporting
confidence: 67%
“… 7 We confirmed significantly higher expression of CD23 molecule on B lymphocytes and their subsets in AD patients with and without dupilumab therapy compared with controls. 7 …”
supporting
confidence: 67%
“…A study by Čelakovská et al investigated immunophenotyping B cells in patients with AD with and without dupilumab treatment. 64 The study found that patients treated with dupilumab had higher CD200 expression on switched B lymphocytes compared to the control group.…”
Section: Admentioning
confidence: 92%